133 Activity and psychosocial health in adolescents with congenital heart disease (CHD). (9th June 2011) - Morrison, M L; Sands, A J; McCusker, C G; McKeown, P P; McMahon, M; Gordon, J; Craig, B G; Casey, F A
Abstract : Many patients with CHD are now adolescents. Like other patients with chronic illnesses they may be at higher risk of psychological/emotional problems. Ability to exercise is an important quality of life measure and indicator of physical health. We aimed to ascertain if activity and psychosocial health were reduced in adolescents with major CHD compared to those with a minor diagnosis. Patients aged 12–20 years were identified using the Northern Ireland regional database (HeartSuite). Participants were categorised as having major or minor CHD and divided into four diagnostic subgroups. Participants completed validated, age-appropriate questionnaires examining standard psychological parameters. Participants also underwent an evaluation of exercise, including formal exercise stress testing and measurement of free-living activity using an ActiGraph accelerometer. Results were analysed using parametric methods. 143 patients (mean age 15.6 years) consented to participate, 86 were male (60%) and 105 had major CHD (73%). Diagnostic subgroups included 39 acyanotic (27.3%), 61 acyanotic corrected (42.7%), 30 cyanotic corrected (21.0%) and 13 (9%) cyanotic palliated patients. Beck Youth Inventory demonstrated that individuals with major CHD, particularly cyanotic palliated patients, had higher anxiety scores (p value 0.01 (−8.42, −1.13)). There were no significant differences across study groups for self-esteem or other psychological parameters. 134 participants (93.7%) took part in regular exercise each week. There was no significant difference in activity score between study groups. On formal exercise testing, more complex patients performed worse at peak exercise. Exercise time for acyanotic group 11.73 mins (sd 3.74) compared to 8.26 mins (sd 4.08) in cyanotic palliated group, p value 0.002 (1.32, 5.61)). However, patients with major CHD had significantly higher activity counts. Correlation analysis showed that self-esteem and health locus of control were important predictor variables for activity. Self-esteem and mood seem well preserved in adolescents with CHD as a whole. The majority of young people with CHD, in this group, take part in regular exercise. Surprisingly, complex patients rate themselves to be as active as those with minor CHD. While accelerometer data indicate that the group may be more active day to day, they are limited in terms of peak exercise duration. The experience of growing up with a chronic condition may therefore have a positive effect on psychological health and interventions targeted around this area may influence activity.